Deteksi Arah Gerak Bola dengan Metode Optical Flow pada Robot Penjaga Gawang - Nova Handika, Rendi; Rahmani, Budi (STMIK Banjarbaru, 2023)
The goalkeeper robot developed by STMIK Banjarbaru still faces challenges in improving the response to the ball to reduce the possibility of goals being scored by opposing robots. The ability of the robot keeper is currently limited to the starting point of the ball so that when the ball bounces toward the goal, the robot has not been able to predict the end point of the ball, resulting in the movement of the goalkeeper robot, which is sometimes slow in blocking the ball. This research was conducted to develop a detection system of a ball direction using the optical flow method. The Logitech C270 series web camera device is used on a robot with a laptop as a video data processor using Python language. The results show that this system is capable of detecting balls in all five directions or quadrants, including 90°, 135°, 180°, 225°, and 270. The detection results of these directions are represented as position information data, such as a ball in a state of still, right, bottom right, top right, left, top left, bottom left, top, and bottom. Keywords: goalkeeper; response; ball direction; robot motion; AbstrakRobot Penjaga gawang yang dikembangkan oleh STMIK Banjarbaru masih menghadapi tantangan dalam meningkatkan respon terhadap bola agar dapat mengurangi kemungkinan terjadinya gol oleh robot lawan. Kemampuan robot keeper saat ini terbatas pada titik awal bola saja, sehingga ketika bola melambung ke arah gawang, robot belum mampu memprediksi titik akhir bola, dan mengakibatkan pergerakan robot goal keeper yang kadang lambat dalam menghalau bola. Penelitian ini dilakukan untuk mengembangkan sistem deteksi arah gerak bola menggunakan metode optical flow. Perangkat kamera web seri Logitech C270 digunakan pada robot dengan sebuah laptop sebagai pengolah data video menggunakan bahasa python. Hasil penelitian menunjukkan bahwa sistem ini mampu mendeteksi bola di kelima arah atau kuadran antara lain 90°, 135°, 180°, 225°, dan 270. Hasil deteksi arah ini direpresentasikan menjadi data keterangan posisi seperti bola pada keadaan ‘diam’, ‘kanan’, ‘kanan bawah’, ‘kanan atas’, ‘kir’i, ‘kiri atas’, ‘kiri bawah’, ‘atas’, dan ‘bawah’.Kata kunci: penjaga gawang; respon; arah bola; gerak robot;